The politics of play in urban design: agamben’s profanation as a recalibrating approach to urban design research (2014)
The paper aims to search for an alternate narrative of urban design within the complexities and the contradictions of the current production of urban spaces. In doing so it adopts a broader conception of design and position the reflection along the thematic context of the informal squat-occupation urban realities. It presents a conceptual elaboration around Giorgio Agamben’s ontology and political aesthetics as an aggregate source toward a possible (re)calibration of the approach to urban design research and practice. Playing with the topos and the gesture of neoliberal urban design, and framing it into the wider background of the current trends of gated urbanisms and hyper symbolic urban regeneration, the paper explores the notion of profanation as act capable to unlock and enhance new modes of politics. The centrality of the act of profanation is seen – through the lenses of a design research initiative in Rome – not simply as a productive antidote to the ‘sacred’ phenomenon of urban design and its gesture imposed on humanity from the above, but as a site of resistance in reclaiming, above all, a capacity of speech for an otherwise displaced and silenced urban subject and, along with it, the intellectual productivity of urban design theory and practice themselves.